2021
DOI: 10.3390/app11199268
|View full text |Cite
|
Sign up to set email alerts
|

A Practice for the Application of Waste in Road Asphalt Pavements in an Eco-Friendly Way

Abstract: The integration of circular economy principles in the design of road pavements raises the problem of obtaining high-performance asphalt mixtures for reduction of waste and environmental pollution compared to traditional solutions. In this study, the base and binder layers of road asphalt pavements were prepared by using reclaimed asphalt pavement and construction and demolition waste as coarse aggregates, while jet grouting waste and fly ash served as fillers. A leaching test was performed for the marginal mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Foreground LCI data sources were mentioned as literature, manufacturer data, and experimental data, whereas background databases (see Figure 11) were predominantly found as ecoinvent (various versions) (n = 41), GaBi (n = 4), EPDs (n = 3), and through the tool tools applied, not specified further, e.g., OneClick LCA (n = 2) and Tally ® (n = 1). The applied background database was found to be inconclusive for (n = 7), whereas some addressed using multiple databases (n = 19), e.g., [65], using ecoinvent, US EPA, and Eurobitumen, [66], using GaBi and SICV Brazil, and [67], using Chinese Life Cycle Database (CLCD) and the European reference Life Cycle Database (ELCD).…”
Section: Embodiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreground LCI data sources were mentioned as literature, manufacturer data, and experimental data, whereas background databases (see Figure 11) were predominantly found as ecoinvent (various versions) (n = 41), GaBi (n = 4), EPDs (n = 3), and through the tool tools applied, not specified further, e.g., OneClick LCA (n = 2) and Tally ® (n = 1). The applied background database was found to be inconclusive for (n = 7), whereas some addressed using multiple databases (n = 19), e.g., [65], using ecoinvent, US EPA, and Eurobitumen, [66], using GaBi and SICV Brazil, and [67], using Chinese Life Cycle Database (CLCD) and the European reference Life Cycle Database (ELCD).…”
Section: Embodiedmentioning
confidence: 99%
“…In this scoping review, we identified 85 primary studies presenting some kind of LCA study within the Built Environment and construction industry with an explicitly de- Most studies did not assess sensitivity (n = 56), see Figure 16, while the ones that did (n = 29) assessed the sensitivity with various approaches and aims. While some assessed the quantitative values of their input data (n = 15), others assessed e.g., the impact of transportation modelling (n = 6), while some applied purpose developed scenarios and prospective assumptions (n = 14), e.g., by testing the modelled number of cycles or the lifespan assumptions [52,55,56,78] by adding additional scenarios [39,58,61,76,79] or by interchanging the allocation or system boundary limitation [39,70,73,80]; one (n = 1) tested the most suitable solution by varying MCDM weights [65]. Some of the studies tested several sensitivity aspects.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…In detail, with the aim of lowering the consumption of nonrenewable raw materials and fossil fuels in the construction and maintenance of asphalt road pavements, researchers are trying to quantify, through internationally consolidated and standardized LCA methodology, the potential environmental impacts and the relative benefits of alternative bituminous materials containing secondary raw materials in substitution of natural ones [ 6 , 7 ], bitumen modification to extend the service life of pavements [ 8 ] and low-temperature production technologies [ 9 , 10 ]. In addition, LCA can be applied for comparison/decision-making purposes to rate the environmental sustainability of different construction and maintenance solutions with alternative asphalt materials versus traditional hot-produced ones [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among other goals, the one mentioned in ninth place in the U.N. 2030 Agenda for Sustainable Development (https://sdgs.un.org/2030agenda, accessed on 23 February 2022) defines short/medium-term objectives centred on building more resilient infrastructure, fostering innovation, and promoting sustainable industrialization. In this sense, as explained by Russo et al [1] when referring to the road infrastructure pavement sector, an appropriate contribution to the fulfilment of this goal can be given by the incorporation of different materials (including waste) that improve the performance of bituminous mixtures. These materials comprise not only a variety of polymers [2] (such as styrene-butadiene-styrene (SBS), poly(ethylene terephthalate) (PET), high-density polyethylene (HDPE), low-density polyethylene (LDPE), polystyrene (PS), polyurethane (PU), polypropylene (PP), crosslinked polyethylene (XLPE or PEX), acrylonitrile butadiene styrene (ABS), ethylene-vinyl acetate (EVA), styrene-isoprene-styrene (SIS), and others), Sulphur, mineral acids, and sustainable polymers from recycled waste plastics [3] but also different types of waxes (natural or synthetic).…”
Section: Introductionmentioning
confidence: 99%
“…1 EN 13924-1:2015[41]; 2 NP EN 12591:2011[42];3 NP EN 14023:2013 [43]. The bracket means that the three lines on the right-hand side are related to only one line (and not three) on the left-hand side.…”
mentioning
confidence: 99%